Allergic diseases and immunodeficiencies in children, lessons learnt from COVID‐19 pandemic by 2022: A statement from the EAACI‐section on pediatrics. Issue 10 (30th September 2022) - Munblit, Daniel; Greenhawt, Matthew; Brough, Helen A.; Pushkareva, Anna; Karimova, Diana; Demidova, Anastasia; Warner, John O.; Kalayci, Omer; Sediva, Anna; Untersmayr, Eva; Rodriguez del Rio, Pablo; Vazquez‐Ortiz, Marta; et al.
Abstract: By the April 12, 2022, the COVID‐19 pandemic had resulted in over half a billion people being infected worldwide. There have been 6.1 million deaths directly due to the infection, but the pandemic has had many more short‐ and long‐term pervasive effects on the physical and mental health of the population. Allergic diseases are among the most prevalent noncommunicable chronic diseases in the pediatric population, and health‐care professionals and researchers were seeking answers since the beginning of pandemic. Children are at lower risk of developing severe COVID‐19 or dying from infection. Allergic diseases are not associated with a higher COVID‐19 severity and mortality, apart from severe/poorly controlled asthma. The pandemic disrupted routine health care, but many mitigation strategies, including but not limited to telemedicine, were successfully implemented to continue delivery of high‐standard care. Although children faced a multitude of pandemic‐related issues, allergic conditions were effectively treated remotely while reduction in air pollution and lack of contact with outdoor allergens resulted in improvement, particularly respiratory allergies. There is no evidence to recommend substantial changes to usual management modalities of allergic conditions in children, including allergen immunotherapy and use of biologicals. Allergic children are not at greater risk of multisystem inflammatory syndrome development, but some associations with Long COVID were reported, although the data are limited, and further research is needed. This statement of the EAACI Section on Pediatrics provides recommendations based on the lessons learnt from the pandemic, as available evidence.